The origins of premium television fiction in Spain. Canal+ and its evolution towards new ways of production and distribution as Movistar+ - Gutiérrez-Lozano, Juan Francisco (Routledge, 2020)
The transformations that the Spanish audio-visual market has experienced in recent decades find in Canal+ España an example that, given the growth of the company, illustrates two of the most significant changes occurred. The first concerns technology itself; the second refers to the increase in the production of original fiction, which has been referred to as the “boom” of Spanish productions. Although paid television was launched in Spain back in 1990, Canal+ Spain invested little in original fiction since. In 2015, Canal+ was taken over by Telefónica, a leading telco, and now, renamed Movistar+, is the undeniable leader in the pay television market. The chapter spotlights how all these changes have affected the main titles of fiction produced and planned by this platform. The entry of new competitors in Spain since 2015 triggered the commission of new abundant original production, branded as “Originales Movistar+”. Through a description of the main characteristics of its “prestige” fiction between 2017–2019, the chapter details how this national case is a prominent example of the transition towards a new global market for the production and circulation of top-quality original fiction.
https://authorservices.taylorandfrancis.com/frequently-asked-questions/open-access-books-faq/
Keywords: Industria audiovisual - España; Television; Platforms; Movistar+; Canal+; Spain